Interband optical transitions in spherical nanoheterostructures - Boichuk, V.I.; Bilynskyi, I.V.; Shakleina, I.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
A spherical semiconductor nanoheterostructure of cubic symmetry is studied in the paper. Accurate solutions of the Schrödinger equation for S₁/₂, P₁/₂, P₃/₂, D₅ /₂, and D₇/₂ states of particles are found in the framework of the Luttinger-Baldereschi-Lipari Hamiltonian and the finite value of the band disruption on the boundaries of the media is ascertained. Specific calculations of the quantum dot radius dependence of the hole state energy were performed for the GaSb/AlSb heterostructure. The obtained results were compared to the data obtained using the infinite potential well model as well as the model of simple bands for heavy and light holes. The electron energies and electron wavefunctions were found within the isotropic effective mass model taking into account a discontinuity of the conduction bandgap on the heterostructure boundary. Probabilities of GaSb/AlSb heterosystem interband transitions were analyzed using the obtained formulae.